Is Innovation in Pakistan Driven by Specialisation or Diversity? (The Pakistan Development Review, 2016)
Innovation is among the main drivers of industrial development leading to economic growth. However, the question triggers that what drives innovation? Is innovation driven by specialisation or diversification? The literature has supported both, the specialisation and diversification as driver of innovation. Therefore, the purpose of this paper is to explore the determinants of innovation in Pakistan with a special emphasis on specialisation and diversity. The analysis is based on the cross sectional data set of 784 firms across 13 different cities of Pakistan, i.e. Investment Climate Survey (ICS) 2007, compiled by the World Bank Enterprise Group. Our findings have showed the positive relation between innovation and diversity i.e. diversity is conducive to innovation. On the other hand, specialisation has a negative effect i.e. it hinders innovation in cities of Pakistan. JEL Classification: C21, C25, O31, O32 Keywords: Innovation, Specialisation, Diversity, Logistic Regression